Pembuatan Lubang Biopori Guna Meningkatkan Resapan Air Hujan Di Dusun Satu A Desa Banjar - Fynnisa Z; Aldi Ramadhan; Arraniri Nasution; Elsa Rahmadani; Heri Setiawan; Muhammad Khoir; Rani Hartini; Samuel Richard Hasian Pakpahan; Wahfi Dahwafi (Jurnal Garuda Pengabdian Kepada Masyarakat, 2024)
Water is a crucial resource, but its management often faces challenges, particularly in terms of rainwater absorption. Dusun Satu A, Desa Banjar, Air Joman Subdistrict, Asahan Regency, North Sumatra Province, faces challenges in managing rainwater due to its lower elevation compared to other dusuns. To address this issue, biopore holes serve as an effective solution. Biopore holes are a water conservation technique involving the creation of holes in the ground to enhance rainwater infiltration, thereby reducing surface runoff and accelerating the absorption of water into the soil. Additionally, biopores can convert organic waste into compost and improve soil fertility.